Investigating the role of shape on the biological impact of gold nanoparticles in vitro. (September 2015) - Tian, Furong; Clift, Martin JD; Casey, Alan; del Pino, Pablo; Pelaz, Beatriz; Conde, João; Byrne, Hugh J; Rothen-Rutishauser, Barbara; Estrada, Giovani; de la Fuente, Jesús M; Stoeger, Tobias
Aim: To investigate the influence of gold nanoparticle geometry on the biochemical response of Calu-3 epithelial cells.Materials & methods: Spherical, triangular and hexagonal gold nanoparticles (GNPs) were used. The GNP-cell interaction was assessed via atomic absorption spectroscopy (AAS) and transmission electron microscopy (TEM). The biochemical impact of GNPs was determined over 72 h at (0.0001–1 mg/ml).Results: At 1 mg/ml, hexagonal GNPs reduced Calu-3 viability below 60%, showed increased reactive oxygen species production and higher expression of proapoptotic markers. A cell mass burden of 1:2:12 as well as number of GNPs per cell (2:1:3) was observed for spherical:triangular:hexagonal GNPs.Conclusion: These findings do not suggest a direct shape-toxicity effect. However, do highlight the contribution of shape towards the GNP-cell interaction which impacts upon their intracellular number, mass and volume dose.